2020
DOI: 10.1186/s13014-020-01523-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adjuvant radiotherapy on the survival of women with optimally resected stage III endometrial cancer in the era of modern radiotherapy: a retrospective study

Abstract: Background: The optimal adjuvant treatment for stage III endometrial cancer in the era of modern radiotherapy remains undefined. We investigated the benefit of adjuvant radiotherapy for women who underwent optimal resection for stage III endometrial cancer in the era of modern radiotherapy. Methods: We retrospectively reviewed patients with endometrial cancer who were treated between 2010 and 2018. Adjuvant treatment included radiotherapy by modern radiotherapy techniques (intensity-modulated or volumetric mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
1
13
1
Order By: Relevance
“…For apparent uterine-confined endometrial carcinoma, the primary treatment was staging surgery, which included total hysterectomy, bilateral salpingo-oophorectomy, selective or systematic pelvic lymphadenectomy, and peritoneal washings [ 7 , 16 ]. The median dissected lymph nodes number was 16 (range: 0–43).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For apparent uterine-confined endometrial carcinoma, the primary treatment was staging surgery, which included total hysterectomy, bilateral salpingo-oophorectomy, selective or systematic pelvic lymphadenectomy, and peritoneal washings [ 7 , 16 ]. The median dissected lymph nodes number was 16 (range: 0–43).…”
Section: Methodsmentioning
confidence: 99%
“…Chemotherapy was administered less frequently than radiotherapy in IB patients. Platinum-based regimens plus paclitaxel were commonly given (75%), while other regimens including cisplatin plus doxorubicin (13%), doxorubicin plus ifosfamide (6%), or epirubicin plus cisplatin (6%) were also administered according to the physician’s preferences [ 7 ]. The median number of administered chemotherapy cycles was four (range: 2–6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we identified that the foremost recent studies with chemo- and RT in EC investigate modern variants of radiation therapy such as proton therapy, intensity-modulated radiation therapy (IMRT) and volume-modulated arc radiotherapy (VMAT), alone or in combination with platinum compounds ( Table 2 ), with results yet to be published in most of the cases. Such modern therapies have the advantage of reducing off-target irradiations [ 126 ] and associated secondary effects in EC [ 127 , 128 ]. Moreover, IMRT and VMAT, alone or combined with chemotherapy, have successfully reduced the risks of recurrence and death in non-endometrioid EC.…”
Section: Current Clinical Trials Employing Agents With Radiosensitmentioning
confidence: 99%
“…Moreover, IMRT and VMAT, alone or combined with chemotherapy, have successfully reduced the risks of recurrence and death in non-endometrioid EC. Patients over 60 years of age as well as those with endometrioid histology, lymphovascular space invasion, and with two or more positive lymph nodes benefitted the most [ 128 ].…”
Section: Current Clinical Trials Employing Agents With Radiosensitmentioning
confidence: 99%